ダイ7ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク コウソウ キショウ カンソク - 石田, 恭市; イシダ, キョウイチ; 清野, 善兵衛; セイノ, ゼンベイ; 清水, 正義; シミズ, マサヨシ; ISHIDA, Kyoichi; SEINO, Zenbei; SHIMIZU, Masayoshi (国立極地研究所, 1967)
P(論文) Syowa Station was officially opened on February 1st, 1966 and routine upper observations by the use of newly-developed rawinsonde (Type RS II-64) were started on February 11th. By January 31st, 1967, 360 sondes in total were released at 1200 GMT, including 3 additional observations at 0000 GMT during the period of stratospheric warming in October 1966. Meteorological elements measured with the sonde attached to 600 gr Latex balloon were : Temperature with bead-type thermistor (0.5-1.0 mm in diameter, 1.0-1.5 mm long), humidity with carbon-type hygrometer (thickness 1mm, size 16×60 mm), and pressure with bellow-type barometer (60 mm in diameter). Signals were received by a D55B Automatic Direction Finder with parametric amplifier, and were printed automatically. Monthly average values of temperature, height, and humidity were computed. Increase in humidity was observed in late summer and the decrease was noticed in late spring, which indicated the change of air mass over Syowa Station. Analysis of mean monthly temperatures at 500mb-level showed that there were pronounced year-to-year variations in all seasons except winter. Mean monthly temperatures at 50 mb-level indicated large year-to-year variations in September, October, and November. In the troposphere and the stratosphere, the southerly wind component prevailed in April-May (autumn) and September-October (spring), and the easterly wind component which was predominant in summer disappeared in the stratosphere during winter. Stratospheric warming started on October 20th from the coast of east Antarctica. Accompanying the movement of the warming centre to the east, the warmed area expanded all over the continent. Circum-polar vortex disappeared on about November 20th and summer type circulation was established. At Syowa Station, changes in wind direction and speed were not observed immediately after the stratospheric warming however, within a month the wind speed decreased gradually and the direction changed from westerly to easterly. departmental ...